Classification Of Pulmonary Pathology From Breath Sounds Using The Wavelet Packet Transform And An Extreme Learning Machine - Sundaraj, Kenneth; Palaniappan, Rajkumar; Sundaraj, Sebastian; Huliraj, N.; Revadi, S. S. (Walter de Gruyter GmbH, 2018)
Background:Auscultation is a medical procedure used for the initial diagnosis and assessment of lung and heart diseases.From this perspective,we propose assessing the performance of the extreme learning machine (ELM) classifiers for the diagnosis of pulmonary pathology using breath sounds.Methods:Energy and entropy features were extracted from the breath sound using the wavelet packet transform.The statistical significance of the extracted features was evaluated by one-way analysis of variance (ANOVA).The extracted features were inputted into the ELM classifier.Results:The maximum classification accuracies obtained for the conventional validation (CV) of the energy and entropy features were 97.36% and 98.37%,respectively,whereas the accuracies obtained for the cross validation (CRV) of the energy and entropy features were 96.80% and 97.91%,respectively.In addition,maximum classification accuracies of 98.25% and 99.25% were obtained for the CV and CRV of the ensemble features,respectively.Conclusion:The results indicate that the classification accuracy obtained with the ensemble features was higher than those obtained with the energy and entropy features.